(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kvitka T. V. The content and structure of self education students of technical schools. In the article analyzed the essence of the concepts of «independent work of students» and «self-educational activities», revealed the difference between them. A sightseeing characteristic components of the structure of self-activity of students of higher technical education establishments, which may be carried out in the study of mathematical disciplines. The author examines the logic of self-organization activities, offers characteristic structurally oriented, information and practice- stimulating creative stages of self, suggests methods of self-educational students based on the characteristics of each of these stages.